Penetapan Harga Sewa Rumah Kos Pada Masa Pandemi Covid-19 di Kota Bukittinggi Perspektif Fiqh Mu’āmalah - Ramadhani Ramadhani (Hakamain: Journal of Sharia and Law Studies, 2022)
This research was written to find out how the practice of setting prices for renting boarding houses during the Covid-19 pandemic in Bukittinggi, because there are differences in setting boarding house rental prices where the boarding house owner waives or waives boarding house rent during the pandemic. However, there are also some boarding house owners who continue to pay full boarding fees as before the Covid-19 pandemic. Furthermore, the author also wants to know how fiqh muāmalah views the pricing of boarding house rents during the Covid-19 pandemic. This study used field research, while the data sources for this research consisted of primary data sources, which were obtained from observations and interviews with students and boarding house owners in the Aur Birugo Tigo Baleh Village. The conclusions from research regarding the pricing of boarding house rentals during this pandemic were found in 3 versions. First, the boarding house owner waived boarding fees during the Covid-19 pandemic. Second, the boarding house owner provides relief by paying half the boarding fee of the pre-pandemic price. Third, boarding house owners do not provide fee relief by continuing to pay full boarding fees during the Covid-19 pandemic. In the view of fiqh muāmalah, leasing or ijārah is legally permissible or permissible as long as there is no argument that forbids it.